Fluctuations in Ammonia Oxidizing Communities Across Agricultural Soils are Driven by Soil Structure and pH - Pereira e Silva, Michele C; Poly, Franck; Guillaumaud, Nadine; van Elsas, Jan Dirk; Falcão Salles, Joana (Frontiers in Microbiology, 2012)
The milieu in soil in which microorganisms dwell is never constant. Conditions such as temperature, water availability, pH and nutrients frequently change, impacting the overall functioning of the soil system. To understand the effects of such factors on soil functioning, proxies (indicators) of soil function are needed that, in a sensitive manner, reveal normal amplitude of variation. Thus, the so-called normal operating range (NOR) of soil can be defined. In this study we determined different components of nitrification by analyzing, in eight agricultural soils, how the community structures and sizes of ammonia oxidizing bacteria and archaea (AOB and AOA, respectively), and their activity, fluctuate over spatial and temporal scales. The results indicated that soil pH and soil type are the main factors that influence the size and structure of the AOA and AOB, as well as their function. The nitrification rates varied between 0.11 ± 0.03 µgN.h-1.gdw-1 and 1.68 ± 0.11 µgN.h-1.gdw-1, being higher in soils with higher clay content (1.09 ± 0.12 µgN.h-1.gdw-1) and lower in soils with lower clay percentages (0.27 ± 0.04 µgN.h-1.gdw-1). Nitrifying activity was driven by soil pH, mostly related to its effect on AOA but not on AOB abundance. Regarding the influence of soil parameters, clay content was the main soil factor shaping the structure of both the AOA and AOB communities. Overall, the potential nitrifying activities were higher and more variable over time in the clayey than in the sandy soils. Whereas the structure of AOB fluctuated more (62.7 ± 2.10%) the structure of AOA communities showed lower amplitude of variation (53.65 ± 3.37%). Similar trends were observed for the sizes of these communities. The present work represents a first step towards defining a NOR for soil nitrification. Moreover, the clear effect of soil texture established here suggests that the NOR should be defined in a soil-type-specific manner.